2012
DOI: 10.1177/0969733011436028
|View full text |Cite
|
Sign up to set email alerts
|

Implied consent and nursing practice

Abstract: Nursing professionals in a variety of practice settings routinely use implied consent. This form of consent is used in place of or in conjunction with informed or explicit consent. This article looks at one aspect of a qualitative exploratory study conducted in a Day of Surgery Admission unit. This article focuses on the examination of nurses' understandings of implied consent and its use in patient care in nursing practice. Data were collected through one-on-one interviews and analysed using a thematic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
1
12
0
4
Order By: Relevance
“…Being that many of the nursing care procedures undertaken in practice have the potential to limit patients’ autonomy, 35 it is important to expand our knowledge on nurses’ opinions and practices regarding information and consent.…”
Section: Introductionmentioning
confidence: 99%
“…Being that many of the nursing care procedures undertaken in practice have the potential to limit patients’ autonomy, 35 it is important to expand our knowledge on nurses’ opinions and practices regarding information and consent.…”
Section: Introductionmentioning
confidence: 99%
“…26 Hemşirenin önemli rollerinden olan savunuculuk, hastanın bilgilendirilmesi ve eğitimi ile yakından ilişkilidir. 37 Cole'nin yaptığı nitel çalışmada, hemşirelerin, hasta özerkliğinin iletişim, bilgilendirme, eğitim ve hemşirelerin savunuculuk rolü ile güçlendirildiğine ve bu faktörlerin, hasta ve hemşire arasında terapötik bir ilişkinin oluşumunu etkilediğine inandıkları belirlenmiştir. 37 Hasta savunucusu olarak hemşirenin, hastasını mantıklı ve anlayarak karar verebilmesi için teşvik etmesi ve desteklemesi gerekmektedir.…”
Section: Discussionunclassified
“…37 Cole'nin yaptığı nitel çalışmada, hemşirelerin, hasta özerkliğinin iletişim, bilgilendirme, eğitim ve hemşirelerin savunuculuk rolü ile güçlendirildiğine ve bu faktörlerin, hasta ve hemşire arasında terapötik bir ilişkinin oluşumunu etkilediğine inandıkları belirlenmiştir. 37 Hasta savunucusu olarak hemşirenin, hastasını mantıklı ve anlayarak karar verebilmesi için teşvik etmesi ve desteklemesi gerekmektedir. Hastalara mantıklı karar verebilmeleri için yapılacak uygulamalara yönelik faydalar, riskler, alternatif yöntemler hakkında yeterli bilgi sağlandıktan sonra herhangi bir bakım uygulaması için onam şarttır.…”
Section: Discussionunclassified
“…Furthermore, nurse researchers must implement an informed consent process that places participants at the center. Participant-centered informed consent must be voluntary and without coercion, given that the patient participant has full comprehension of what is involved (Cole, 2012). Tomlin et al (2012) reported that although nurse researchers primarily identify themselves as clinicians, ethical standards of informed consent processes are inconsistently upheld.…”
Section: Implications For Nursing Researchmentioning
confidence: 99%